2021
DOI: 10.1177/00336882211044878
|View full text |Cite
|
Sign up to set email alerts
|

One Does Not Simply Teach Idioms: Meme Creation as Innovative Practice for Virtual EFL Learners

Abstract: To maximize the advantages of virtual learning, the present study highlights the potential for Internet meme design and creation in English language learning (ELL) courses as an innovative activity that raises student agency, increases multimodal literacy, inculcates intercultural communication, and teaches idiomatic expression. Memes resonate a multimodal feedback loop of popular culture. In the context of language education, multimodal literacy is a necessity for 21st-century education because the affordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This article reviewed 20 empirical studies on digital multimodal composing, especially to examine the DMC tasks implemented in the post-secondary EFL context and what implications are yielded from the implementations. Borrowing from the research strands found in Li and Akoto (2021), the findings showed that the DMC projects practiced in the post-secondary EFL context involved multimodal appropriating such as meme creation (Smith, 2021) and multimodal presentation (Seau, Azamn, & Noor, 2018), multimodal remixing and code-meshing such as mixing cultural resources (Jiang, 2022), and voice/identity/attitude expression such as learning investment and identity development of EFL learner from ethic Chinese minority group (Jiang, Yang, & Yu, 2020) and students' willingness to participate (Shen, Hao, & Peng, 2022). The results on DMC tasks in the studies were reported to afford students' improvement on digital literacy skills, English language skills, engagement and investment, critical thinking and creativity, and overall attitude in composing.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This article reviewed 20 empirical studies on digital multimodal composing, especially to examine the DMC tasks implemented in the post-secondary EFL context and what implications are yielded from the implementations. Borrowing from the research strands found in Li and Akoto (2021), the findings showed that the DMC projects practiced in the post-secondary EFL context involved multimodal appropriating such as meme creation (Smith, 2021) and multimodal presentation (Seau, Azamn, & Noor, 2018), multimodal remixing and code-meshing such as mixing cultural resources (Jiang, 2022), and voice/identity/attitude expression such as learning investment and identity development of EFL learner from ethic Chinese minority group (Jiang, Yang, & Yu, 2020) and students' willingness to participate (Shen, Hao, & Peng, 2022). The results on DMC tasks in the studies were reported to afford students' improvement on digital literacy skills, English language skills, engagement and investment, critical thinking and creativity, and overall attitude in composing.…”
Section: Discussionmentioning
confidence: 92%
“…The DMC tasks that were described in the studies incorporated the use of various multimodal resources to create videos (e.g., Kim & Belcher, 2020;Chen, 2018;Jiang, 2018), to develop presentation materials (e.g., Li, 2022;Seau, Azamn, & Noor, 2018;Shen, Hao, & Peng, 2022), to write collaboratively (e.g., Zenouzagh, 2022), and to create memes (e.g., Smith, 2021). In addition, there was one study focusing on students' DMC tasks within the researcher's developed application (Lin et al, 2021) and one study focusing on the resemiotization of one type of text into another one (Lo, Lee, & Tien, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this challenge also presents an opportunity. If harnessed effectively in EFL pedagogy, these idiomatic expressions can serve as gateways to deeper linguistic understanding, cultural immersion, and authentic language engagement (Namaziandost et al, 2021;Smith, 2021;Rodríguez-Muñoz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A case in point is Al-Ramahi and Smadi's study [12] suggesting that video games could positively influence the learning of idioms, as they raise students' motivation and force them to use idiomatic expressions in an authentic context while interacting with other players. In the same vein, Smith [13] examined meme design and creation as a novel activity for fostering students' autonomous learning, multimodal literacy, instilling intercultural communication and mastering idiomatic expressions. With regard to messaging apps, Batianeh [14] explored the effects of utilizing online chats together with word processors on the students' writing skills, including aspects as punctuation, phrasal verbs, idioms and figures of speech, among others.…”
Section: Introductionmentioning
confidence: 99%